The Analysis Of Implementation Of Permit To Work at Height in the Projects PT. X year 2023 - Saragih, Kurniawan Syahrimbun; Dewi, Fitri; Kafit, Muhammad (Universitas Muhammadiyah Kalimantan Timur, 2024)
World developments influence to all sectors, including the development sector which is also increasingly rapid and with the application of increasingly sophisticated technology, the application of Occupational Health and Safety is one of the main requirements for work that must be taken into account. is one of the contractors engaged in the construction sector where its activities cannot be separated from working at heights, So it is necessary to carry out observations and observations in the field regarding